"Málaga Moderna": Suburban Development in Late Nineteenth and Early Twentieth Century Andalucía. (2nd July 2020) - Barke, Michael; Mowl, Graham; Shields, Graham
ABSTRACT: Suburban development was not a common feature of the built form of Spanish cities in the nineteenth century but Málaga experienced significant suburban growth at its eastern periphery in the late nineteenth and early twentieth centuries. The physical development of the suburbs will be examined, stressing the role of key individuals and the influences upon them. The physical character of the suburbs and their subsequent changes were strongly influenced by national and local events which impacted upon the nature of the built environment. However, the social composition of the area did not necessarily reflect the growth of a "new" urban elite as many families retained additional residential premises in the core. The promotion of Málaga as a tourism resort also had a significant impact on the social composition of the area producing a type of suburb rather different from the permanent single-family dwelling middle-class environment typical of northern Europe.